Pengaruh Leverage, Aktivitas, dan Ukuran Perusahaan terhadap Pertumbuhan Laba di Perusahaan Properti dan Real Estate BEI 2019-2023 - Malik Alfi Kurniawan; Rinny Meidiyustiani (Kajian Ekonomi dan Akuntansi Terapan, 2024)
The research carried out has the aim of knowing the effect of the variables Leverage, Activity, and Company Size, on Earnings Growth. the sample taken as research material is the Property and Real Estate Sector companies that have entered the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The sample was selected by considering the use of the purposive sample method. The research conducted utilizes multiple linear regression analysis methods with the Statistical Pakcage for the Social Science (SPSS) Version 25 program. The findings in this research explain that debt equity ratio and company size have no effect on profit growth, while total asset turnover affects profit growth.